1998
DOI: 10.1021/tx980056v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Bay Region Halohydrins Derived from Benzo[a]pyrene Diol Epoxide and Their Role as Intermediates in Halide-Catalyzed Cis Adduct Formation

Abstract: The bay region epoxide of benzo[a]pyrene (anti-BPDE) alkylates DNA to form adducts with >98% trans stereochemistry. Halide ions catalyze this reaction; however, this pathway is characterized by the formation of adducts with altered cis stereochemistry. Bay region halohydrins are possible intermediates in these reactions, but are too unstable to be isolated from aqueous solutions. However, we successfully synthesized halohydrins in tetrahydrofuran (THF) by treatment of anti-BPDE with the corresponding lithium h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…To explain the different tetrol product ratios formed from the reaction of diol epoxide 1 in solutions containing chloride ion, it was proposed that a trans chlorohydrin 5 is formed as a reactive intermediate from the reaction of carbocation 2 with chloride ion, and that 5 hydrolyzes to form cis and trans tetrols in a ratio different than that formed from the reaction of 1 in the absence of chloride ion (Scheme 1). This proposed mechanism was confirmed by the independent synthesis of chlorohydrin 5 and a study of its hydrolysis reactions. , Chlorohydrin 5 is highly reactive toward hydrolysis and yields tetrols in the same ratio as that formed from the reaction of diol epoxide 1 in solutions containing sufficient concentrations of chloride ion.
…”
Section: Introductionmentioning
confidence: 74%
“…To explain the different tetrol product ratios formed from the reaction of diol epoxide 1 in solutions containing chloride ion, it was proposed that a trans chlorohydrin 5 is formed as a reactive intermediate from the reaction of carbocation 2 with chloride ion, and that 5 hydrolyzes to form cis and trans tetrols in a ratio different than that formed from the reaction of 1 in the absence of chloride ion (Scheme 1). This proposed mechanism was confirmed by the independent synthesis of chlorohydrin 5 and a study of its hydrolysis reactions. , Chlorohydrin 5 is highly reactive toward hydrolysis and yields tetrols in the same ratio as that formed from the reaction of diol epoxide 1 in solutions containing sufficient concentrations of chloride ion.
…”
Section: Introductionmentioning
confidence: 74%
“…Sample chromatograms for adducts from (+)- and (−)- anti -BPDE are shown in Figure . Previous work in our lab has shown that the relative and absolute yields of cis anti -BPDE adducts are increased by the addition of halide to the reaction mixture ( ) or by increasing the temperature of the reaction (). The effects of chloride ion and temperature on adduct yield are shown in Figures and , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work in our lab has shown that the formation of cis anti -BPDE products is catalyzed by halide ions ( ). The halide effect arises from partial conversion of BPDE into a trans halohydrin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations